MODERN TRENDS IN IMPLEMENTING DIGITAL TECHNOLOGY IN LANGUAGE TEACHING: INNOVATIONS, CHALLENGES, AND PEDAGOGICAL SHIFTS - Nilufar Giyazova Shoir qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The integration of digital technology in language teaching has revolutionized how languages are taught and learned in higher education. Moving beyond traditional classrooms, educators now use virtual platforms, AI-powered tools, gamified applications, and mobile-assisted learning to enhance engagement, accessibility, and learner autonomy. This study explores recent trends in digital language education, drawing on literature, case studies, and evolving pedagogical models. Particular attention is paid to the practical implications for educators and learners in contexts like Uzbekistan, where digital transformation is a growing priority. The findings reveal both the pedagogical benefits and institutional challenges of embedding digital tools in language teaching.